Assessing ADHD Symptoms among Young Adults in the University with the ASRS v1.1: Examining Associations with Social Anxiety and Self-Efficacy. Issue 5 (3rd September 2022) - Waite, Roberta; Buchanan, Tom; Leahy, Meghan
ABSTRACT: Background: Students with ADHD symptoms in post-secondary settings often go undiagnosed which can contribute to challenges for their overall academic success. The objectives of this study were twofold: (1) examine results of the ADHD Adult Self-Report Scale (ASRS-v1.1, Part A) comparing ADHD symptoms to self-report diagnosis and (2) analyse the association of self-efficacy and anxiety for subjects who scored 4 or more on the ASRS-v1.1. Methods: A sample of 553 students from a university in southern United States was analysed. The ASRS-v1.1, Part A, six items from the Global Self-efficacy Scale, and two subscales of 6 items each from the Liebowitz Social Anxiety Index were used. Results: Participants with a score of 4 or higher on the ASRSv1.1, Part A represented symptomology associated with Adult ADHD. ANOVA results showed participants in the group with 4 or more reported lower self-efficacy and higher scores on the anxiety measures. The OLS regression results also indicated ASRS scores were positively associated with the outcomes.